FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREHIPERTENSI PADA USIA DEWASA DI WILAYAH KERJA PUSKESMAS PELABUHAN SAMBAS KOTA SIBOLGA TAHUN 2017 - Lisandy Yunita Nababan; Rasmaliah .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Prehypertension is blood pressure at intervals of 120-139 mmHg for systolic pressure or 80-89 mmHg for diastolic pressure. Prehypertension is considered as a starting point in the sustainability of hypertension or other cardiovascular diseases. Prehypertension and hypertension are diseases unit caused by various risk factors. The purpose of this research is to determine the factors associated with the incidence of prehypertension in adulthood in the working area of Sibolga Pelabuhan Sambas Health Center in 2017. This research was analytic study using cross-sectional design. The number of sample was 109 person without hypertension in age of 18-40 years old, that took by purposive sampling. The research instrument was questionnaire, tensionmeter, weight and height measurer, and direct observation. The univarian data was analyzed by descriptive test, bivarian data was analyzed by Chi-square test with 95% CI, and multivarian data was analyzed by Binary Logistic Regression test. The result of this research shows that the proportion of prehypertension prevalence in adulthood in the working area of Sibolga Pelabuhan Sambas Health Center in 2017 was 49,5%. There was significant correlation between age (p=0,011), family history (p = 0.0001), obesity (p = 0.0001), and salt intake (p = 0.010) with prehypertension, and family history (Exp.B = 8,669) as the most dominant risk factor of prehypertension in adulthood in the working area of Sibolga Pelabuhan Sambas Health Center in 2017. To the public is expected to maintain the diet, to increase a healthy lifestyle, and to avoid risk factors that can lead to prehypertension or hypertension. To the Health Center is expected to increase counseling about the importance of maintaining a healthy lifestyle and avoid risk factors that can lead to prehypertension or hypertension. Key words: prehypertension, risk factor, family history, obesity, age, salt intake